2012
DOI: 10.1182/blood-2012-04-425207
|View full text |Cite|
|
Sign up to set email alerts
|

A humanized single-chain antibody against beta 3 integrin inhibits pulmonary metastasis by preferentially fragmenting activated platelets in the tumor microenvironment

Abstract: Platelets play a supportive role in tumor metastasis. Impairment of platelet function within the tumor microenvironment may provide a clinically useful approach to inhibit metastasis. We developed a novel humanized single-chain antibody (scFv Ab) against integrin GPIIIa49-66 (named A11) capable of lysing activated platelets. In this study, we investigate the effect of A11 on the development of pulmonary metastases. In the Lewis lung carcinoma (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…Platelets have been suggested to play an important role in cancer progression and metastasis (18). A previous study demonstrated that preliminarily activated platelets have tumor-promoting properties (19). Although the number of studies that have investigated the biological association between MPV and cancer progression is limited, recent clinical reports demonstrated the negative effect of a low MPV on the prognosis of cancer patients.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…Platelets have been suggested to play an important role in cancer progression and metastasis (18). A previous study demonstrated that preliminarily activated platelets have tumor-promoting properties (19). Although the number of studies that have investigated the biological association between MPV and cancer progression is limited, recent clinical reports demonstrated the negative effect of a low MPV on the prognosis of cancer patients.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…Tumour cells can induce platelet activation through various mechanisms and their metastatic potential correlates with their ability to activate platelets [37][38][39][40] . Pharmacological inhibition of platelet activation 41 , or depletion 5 or inhibition 42 of proteins critical for platelet activation significantly decreased the metastatic potential of tumour cells. To test whether the metastasis-enhancing effect of platelet was dependent on TLR4, WT and TLR4 À / À mice were treated with two mechanistically different antiplatelet agents.…”
Section: Experimental Metastasis Is Diminished In Tlr4-deficient Micementioning
confidence: 99%
“…The relationship between increased lymphocyte ratio on the tissue level and good prognosis has Thrombocytosis occurs after megakaryocytes stimulated by pro-inflammatory cytokines such as IL-1 and IL-6 and is considered an indicator of inflammation severity (15). Activated platelets release angiogenic growth factors and contribute to tumor angiogenesis and progression (16). Based on this idea, platelets are thought to play a significant role in cancer growth and metastasis (17), as a result of which MPV is considered a parameter that indicates inflammation (18) and is used for early detection of platelet activation (19).…”
Section: Discussionmentioning
confidence: 99%